2017
DOI: 10.1038/srep40800
|View full text |Cite
|
Sign up to set email alerts
|

Proteoliposomal formulations of an HIV-1 gp41-based miniprotein elicit a lipid-dependent immunodominant response overlapping the 2F5 binding motif

Abstract: The HIV-1 gp41 Membrane Proximal External Region (MPER) is recognized by broadly neutralizing antibodies and represents a promising vaccine target. However, MPER immunogenicity and antibody activity are influenced by membrane lipids. To evaluate lipid modulation of MPER immunogenicity, we generated a 1-Palmitoyl-2-oleoylphosphatidylcholine (POPC)-based proteoliposome collection containing combinations of phosphatidylserine (PS), GM3 ganglioside, cholesterol (CHOL), sphingomyelin (SM) and the TLR4 agonist monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…However, recent work by Luis et al showed that addition of combinatory PS/GM3 (ganglioside of mono-sialic acid) into the Ag-loaded POPC liposomes remarkably increased the anti-Ag immune reactions in vaccinated mice, though insertion of PS alone into the carrier made a minimal contribution to the enhancement [97]. Also, Cauvi et al revealed in murine model that anionic empty PS liposomes triggered peritoneal MPs to have about 4700 genes specifically modified, resulting in changed protein expressions by peritoneal cells, including increased secretion of several chemokines (CXCL1, CXCL2, CSF-2, and CSF-3) and cytokines (TNF-a, IL-6, IL-10).…”
Section: Surface Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work by Luis et al showed that addition of combinatory PS/GM3 (ganglioside of mono-sialic acid) into the Ag-loaded POPC liposomes remarkably increased the anti-Ag immune reactions in vaccinated mice, though insertion of PS alone into the carrier made a minimal contribution to the enhancement [97]. Also, Cauvi et al revealed in murine model that anionic empty PS liposomes triggered peritoneal MPs to have about 4700 genes specifically modified, resulting in changed protein expressions by peritoneal cells, including increased secretion of several chemokines (CXCL1, CXCL2, CSF-2, and CSF-3) and cytokines (TNF-a, IL-6, IL-10).…”
Section: Surface Propertymentioning
confidence: 99%
“…Luis et al using a HIV-1 gp41 MPER (membrane proximal external region) engrafted with tetanus toxoid (TT) as Ags, and POPC (1-palmitoyl-2-oleoylphosphatidylcholine) as the matrix material, prepared the Ag-loaded liposomes as a VADS against HIV. To enhance efficacy, the liposomes were further incorporated with other lipids, including PS (phosphatidylserine), GM3, or combinatory CHO/SM (sphingomyelin) which are enriched in HIV viral membrane lipid rafts, where MPER is embedded for maintaining peptide conformation [97]. In mice, the gp41-TTloaded POPC liposomes when combined with PS/GM3 or CHO/SM induced significantly increased anti-gp41 immune reactions which was further enhanced by the addition of MPLA.…”
Section: Membrane Fluiditymentioning
confidence: 99%
“…Given that the complete epitope of anti-MPER bNAbs includes membrane components ( 74 , 89 ) and that lipid recognition by CDR H3 impacts into their functionality ( 69 , 72 , 73 , 86 , 87 ), their potential for contributing to MPER-specific neutralizing responses by immunization is worth exploring. In this regard, membrane-mimicking platforms including viral-like particles (VLP) ( 137 , 138 ) or liposomes ( 122 124 ) have been approached. It has been shown that membrane lipids can modulate the MPER structure likely by promoting a native-like conformation and demonstrated to improve immunogenicity ( 123 , 124 ).…”
Section: Eliciting Anti-mper Antibodies By Immunizationmentioning
confidence: 99%
“…In this regard, membrane-mimicking platforms including viral-like particles (VLP) ( 137 , 138 ) or liposomes ( 122 124 ) have been approached. It has been shown that membrane lipids can modulate the MPER structure likely by promoting a native-like conformation and demonstrated to improve immunogenicity ( 123 , 124 ). In particular, we previously demonstrated that those lipids overrepresented in the viral membrane such as cholesterol and sphingomyelin have the potential to induce stronger antibody titers comparing with simple POPC lipids ( 124 ).…”
Section: Eliciting Anti-mper Antibodies By Immunizationmentioning
confidence: 99%
“…Arg 696 has been suggested to play a structural role in trimerization by forming polar contacts within the membrane, either alone or in combination with a GxxxG motif, and computational studies on the gp41 TM domain support this claim. 9,[12][13][14] Biophysical studies on the HIV TM have yielded inconsistent results on the oligomeric state of this domain. An NMR analysis of a TM peptide in a DMPC/DHPC mixed micelle showed no evidence of trimerization, but the specific transmembrane peptide used in that study contained significant portions of the MPER and cytoplasmic tail.…”
Section: Introductionmentioning
confidence: 99%